International legal problems in the peaceful exploration and use of outer space - Andem, Maurice N. (Lapin yliopiston oikeustieteellisiä julkaisuja, ISSN 0788-7590, 1992)
Conclusions and observations (s. 404-427).
Keywords: avaruus; avaruusoikeus; demilitarisointi; ilmatila; kansainvälinen oikeus; satelliitit; viestintä